2012
DOI: 10.2337/dc11-1955
|View full text |Cite
|
Sign up to set email alerts
|

More Impact of Microalbuminuria on Retinopathy Than Moderately Reduced GFR Among Type 2 Diabetic Patients

Abstract: OBJECTIVEThe current study aimed to investigate whether microalbuminuria or moderately decreased glomerular filtration rate (GFR) is a better predictor for the development and progression of retinopathy in type 2 diabetic patients.RESEARCH DESIGN AND METHODSType 2 diabetic patients without cardiovascular diseases, malignancy, pregnancy, and acute intercurrent illness were enrolled between 1 August 2001 and 31 December 2002. All participants provided their detailed medical history and underwent an eye fundus ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 30 publications
3
86
2
1
Order By: Relevance
“…However, many factors such as exercise, hypertension and hyperglycemia can influence daily urinary albumin excretion. 32 Even the UACR values are less than the recommended cutoff value (30 mg/g); we emphasize the importance of regular follow-up of UACR in old subjects with low plasma ghrelin levels. 30,31 No previous study has reported the association between the UACR values and ghrelin/obestatin concentrations.…”
Section: Discussionmentioning
confidence: 76%
“…However, many factors such as exercise, hypertension and hyperglycemia can influence daily urinary albumin excretion. 32 Even the UACR values are less than the recommended cutoff value (30 mg/g); we emphasize the importance of regular follow-up of UACR in old subjects with low plasma ghrelin levels. 30,31 No previous study has reported the association between the UACR values and ghrelin/obestatin concentrations.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, we need to perform ophthalmological examination to detect DR carefully, especially in the patients with normo- or microalbuminuria, to identify persons at higher risk of developing macroalbuminuria. It has not been shown that DR itself is related to renal function decline, although some reports have shown that urinary abnormalities, microalbuminuria, or macroalbuminuria predicts DR (26), and microalbuminuria has been indicated to have a greater impact on predicting DR than GFR decline in type 2 diabetic patients (27). …”
Section: Discussionmentioning
confidence: 99%
“…This correlation may be explained by assuming that the appearance of microalbuminuria is a sign of a general vascular dysfunction, including retinal vascular dysfunction. (12,13) In our study, 34 (82.9%) of the patients entering the study had proteinuria of +1, which could explain the positive correlation between the degree of cortex echogenicity and the degree of retinopathy. Albuminuria and associated complications appear to be primarly caused by enzymes with a susceptibility to hyperglycemia, that are involved in the metabolism of anionic components of the extracellular matrix (eg heparan sulfate proteoglycan).…”
Section: Discussionmentioning
confidence: 83%